PHY domain governs structural and photochemical fidelity in the far-red-absorbing state of phytochromes - Fischer, Tobias; Köhler, Lisa; Trunk, Florian; Xu, Qian-Zhao; Zhao, Kai-Hong; Rohr, Valentin; Matysik, Jörg; Gärtner, Wolfgang; Wachtveitl, Josef; Song, Chen; Slavov, Chavdar (Frontiers in Molecular Biosciences, 2026)
BackgroundDespite its central role in signaling, the influence of protein architecture on phytochrome structure and reactivity remains poorly understood. Here, we test how removal of the PHY domain reshapes the far-red–absorbing Pfr energy landscape and photochemical branching in the knotless phytochrome All2699g1g2.MethodsWe combined femtosecond transient absorption (TA) spectroscopy with solid-state NMR to compare Pfr chromophore conformations and photodynamics in a GAF1–PHY construct versus the isolated GAF1 domain. Model-independent lifetime density maps and kinetic modeling were used to resolve the relaxation pathways and the population-weighted photoproduct yields.ResultsGAF1–PHY displays a single chromophore conformation with homogeneous photodynamics and a photoconversion quantum yield of 16%. In contrast, GAF1-only exhibits three ground-state subpopulations (NMR) and heterogeneous photodynamics (TA), with kinetically distinct excited-state behaviors and markedly different branching toward Lumi-F photoproduct formation. One subpopulation accounts for ∼95% of photoproduct formation, whereas the other two relax predominantly through nonproductive recovery, yielding an overall photoconversion quantum yield of ∼10%. The productive branch shows a strongly red-shifted stimulated emission consistent with transient deprotonation at ring C or D, and the GAF1-only photoproduct exhibits CBCR-like electronic rearrangements relative to the canonical PHY-stabilized pattern.ConclusionThe PHY domain acts as a structural gatekeeper that suppresses intrinsic chromophore heterogeneity and directs Pfr excited-state evolution into a defined, productive photoconversion pathway. These findings provide a mechanistic foundation for domain-level control of photoreceptor function and future engineering of light-responsive proteins and optogenetic tools.